2018
DOI: 10.3390/md16120482
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Composite Supplement Containing Collagen Peptide and Ornithine on Skin Conditions and Plasma IGF-1 Levels—A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Aging-associated changes of skin conditions are a major concern for maintaining quality of life. Therefore, the improvement of skin conditions by dietary supplementation is a topic of public interest. In this study, we hypothesized that a composite supplement containing fish derived-collagen peptide and ornithine (CPO) could improve skin conditions by increasing plasma growth hormone and/or insulin-like growth factor-1 (IGF-1) levels. Twenty-two healthy Japanese participants were enrolled in an 8-week double-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 55 publications
1
51
0
Order By: Relevance
“…Similar results on the improvement of the skin were obtained by Ito et al [109] in 40 healthy women by the ingestion of 30-mL of fish-derived collagen and ornithine (CPO) drink. After eight weeks of supplementation, skin elasticity increased in CPO treatments.…”
Section: Improvement Of Skin Propertiessupporting
confidence: 80%
“…Similar results on the improvement of the skin were obtained by Ito et al [109] in 40 healthy women by the ingestion of 30-mL of fish-derived collagen and ornithine (CPO) drink. After eight weeks of supplementation, skin elasticity increased in CPO treatments.…”
Section: Improvement Of Skin Propertiessupporting
confidence: 80%
“…Marine‐based collagen scaffold has applications in bone (TE), [ 74–76 ] wound healing, [ 77 ] food, and nutraceuticals and nutricosmetic. [ 78–82 ]…”
Section: Source Of Collagenmentioning
confidence: 99%
“…[11][12][13][14][15] In addition to the extraction from land animals, to date, marine-derived collagen has also been highlighted in different fields considering redevelopment of 75% of fish waste materials (eg, bone and scale) and the benefits of unique collagen peptides (eg, Ala-Hyp-Gly and Ser-Hyp-Gly). [16][17][18][19] The efficacy of oral hydrolyzed fish collagen for retarding skin aging has been unveiled by several clinical studies as indicated by improvement of skin parameters, such as hydration, wrinkles, pores, or collagen content in human skin. [20][21][22][23][24][25][26][27][28] Furthermore, Djulis has recently been identified as a potential ingredient for skin improvement.…”
mentioning
confidence: 99%